Analisa Wacana Kritis Fenomena MCA (Muslim Cyber Army) Pasca Aksi Bela Islam di Instagram - Lestari, Puput (FIKRAH, 2018)
This research focuses on phenomenon about MCA (Muslim Cyber Army) or in another term it is called as media army who has duty to convoy, to filter, even to clarify such issues or information which spread in social media especially in Instagram. The objective of this research is very simple, they are to find and to know what thing that cause the emergence of MCA accounts. The researcher observes almost all groups who name themselves as Islam have Instagram account that work as MCA. The researcher uses Instagram as the object of research. The researcher uses critical discourse analysis method to analyze every Instagram account that have influence in spreading issues or some posts which cause controvertion and conflict. Finally, the researcher finds that accounts that name themselves as MCA start to emergence after the action of caring Islam. It can be found a hypothesis that there is a group that is not satisfied toward the cases that start the action of caring Islam, therefore, it implicates the emergence of movement to get support from society through Instagram media to disperse mission of that group.